Functional and Results from Nail Lengthening with the Eponychial Folding Procedure Reconstruction of the Fingertip Amputation - Hemphomraj, Thepraksa (Journal of Southeast Asian Orthopaedics, 2021)
Purpose: Fingertip amputation usually involved soft tissue, bone, and nail. Various local flaps reconstruct only soft tissue volar pulp dose not restore nail length after fingertip amputation. To overcome this problem “The Eponychial Folding Procedure” lengthens the nail plate and restore a good appearance of the nail apparatus was employed. The purposes of this study were present the outcomes of nail salvage by Eponychial Folding Procedure combined with several local flaps following fingertip amputation. Methods: In the period between January 2018 and October 2019 at Samutsakorn Hospital. 30 cases of fingertip amputation with nail bed defects underwent pulp reconstruction with different local flaps depending on the geometry of the amputated digit tip. We increased nail bed exposure by creating 4-6 mm parallel incision at distal eponychium. The eponychium flap was elevated then fold proximally to expose more nail matrix, thereby effectively lengthening the exposed nail bed. The outcomes for fingertip appearance, nail length, and nail bed area at pre and postoperative treatment were evaluated. The finger’s range of motion (ROM) was compared to the contralateral uninjured fingers as control. The paired t test was employed for α<.05 considered statistically significant Results: There were 25 patients (5 patients were affected 2 fingers) with mean age of 31 (18-51 years). The procedures were performed initial injury and secondary treatment after consequence previous operation, neither pulp reconstruction nor eponychial flap loss occurred. The visible nail increased 5.78 mm (4-7mm), nail bed area was enlarged 60% (25-150%). All patients were satisfied with the appearance and function of the reconstructed fingertips. Conclusions: Fingertip amputation with nail bed involvement should be reconstructed not only volar soft tissue but considered the nail as well. Eponychial folding Procedure combined with different local flaps provided for the aesthetic and functional restoration of the fingertip amputation, both initial injury and its consequence.